Long-term results with the laparoscopic transposition of renal lower pole crossing vessels. Issue 4 (August 2015) - Villemagne, T.; Fourcade, L.; Camby, C.; Szwarc, C.; Lardy, H.; Leclair, M.-D.
Summary Background For the treatment of ureterovascular pelviureteric junction obstruction (PUJO), transposition of lower pole crossing vessels (LPCV) has been described as an alternative to dismembered pyeloplasty. Purpose To report on the long-term follow-up of children after laparoscopic transposition of LPCV. Methods A retrospective analysis of 70 children consecutively treated by laparoscopic transposition of LPCV. Candidate patients were selected on the basis of clinical history, renal ultrasound (US), and pre-operative mercaptoacetyltriglycine (MAG-3) scan. Selection criteria included: presence of LPCV with SFU Grade 1–2 hydronephrosis, impaired drainage on MAG-3 and intraoperative normal pelviureteric junction (PUJ) and ureter peristalsis. Thinned parenchyma, impaired renal function, or history of prenatal hydronephrosis were not considered as exclusion criteria. Children were clinically followed up with US and MAG-3 scan. Success was defined by symptom resolution with improvement in hydronephrosis. Results Seventy children, aged 8.3 years (range 2.75–16.0), were selected. Procedures were performed through transperitoneal laparoscopy (n = 42) or were robotic-assisted (n = 28). Operative time was 120 min and length of hospital stay was 2 days. The outcome was successful in 67/70 patients (96%), with a median follow-up of 52 months (range 13–114). There were three failures in children who eventually underwent dismembered pyeloplasty for a symptomatic, undiagnosed, intrinsic PUJ obstruction. Two of them had been postnatally followed for a resolving prenatally diagnosed hydronephrosis. Three children became free of symptoms, had improved hydronephrosis, but still showed impaired drainage on MAG-3 and are being closely followed up. Discussion Although this procedure proves to have long-term efficiency in selected indications, the main challenge is to intraoperatively ascertain the absence of associated intrinsic stenosis. Objective criteria remain difficult to establish, but intraoperative findings, including dependent, funnel-shaped, normal-looking PUJ with decreasing hydronephrosis after pelvis and LPCV mobilisation, and efficient peristalsis across the PUJ under intraoperative diuretic test, represent a low likelihood of associated intrinsic stenosis. Ipsilateral impaired renal function doesn't seem to be associated with an adverse outcome. In contrast, a prenatal history of mild or self-resolving hydronephrosis in a patient later presenting with intermittent dilatation, raises the suspicion of associated intrinsic PUJ obstruction, as it is associated with a higher risk of failure. Conclusion With a long postoperative follow-up, the robotic-assisted or laparoscopic vascular hitch procedure has been successful in treating a selected group of children with obstructive LPCV, and represents a safe and reliable alternative to standard dismembered pyeloplasty in the absence of intrinsic PUJO suspected on prenatal US. <table-wrap id="undtbl1" position="anchor"> Table Laparoscopic Transposition of Lower-pole crossing vessels Patients 70 Age at surgery (years) 8.3 [2.75–16] Male/female 44/26 Pre-natal history of hydronephrosis 9 (13%) Pre-operative US pelvis AP diameter (mm) 33 [16–60] Pre-operative Mag-3 impaired ipsilateral function (45%) 32 (46%) Laparoscopic/robotic-assisted procedure 42/28 Duration of procedure (minutes) 120 [60–280] Follow-up (months) 52 [13–114] Complications Clavien IIIb (failure) 3 Clavien IIIb (urinoma) 1 Clavien I 2 Success 67 (96%) </table-wrap>